2000
DOI: 10.1002/1097-0088(20000630)20:8<899::aid-joc433>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

A study of the Urban Heat Island of Granada

Abstract: In this study we examine the Urban Heat Island (UHI) of Granada. First, we perform a study of the evolution of the recorded temperatures at a meteorological station over the last century. In this record, the minimum temperatures increase while the maximum temperatures decrease. We also compare both rural and urban temperature records, obtaining the UHI fluctuations on a smaller time scale. The results show that the UHI phenomenon is stronger in winter, and the maximum difference occurs in early morning when te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
103
0
22

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(135 citation statements)
references
References 19 publications
(33 reference statements)
10
103
0
22
Order By: Relevance
“…The surface roughness increase is associated with accelerations produced by a welldeveloped UHI. This result agrees well with the findings of Chandler (1965), Bornstein and Johnson (1977) and Montavez et al (2000).…”
Section: Resultssupporting
confidence: 93%
“…The surface roughness increase is associated with accelerations produced by a welldeveloped UHI. This result agrees well with the findings of Chandler (1965), Bornstein and Johnson (1977) and Montavez et al (2000).…”
Section: Resultssupporting
confidence: 93%
“…An adjustment of the urban effect is necessary to attain realistic results concerning thermal evolution and changes for large cities. The urban effect usually is greatest during the minimum temperatures in the early morning and under anticyclonic conditions (Montávez et al, 2000;Unger, 1996;Colacino and Lavagnini, 1982). Consequently, it also depends on the season: Yagüe et al (1991) found a strong urban effect in Madrid in summer and a weaker effect in spring.…”
Section: The Urban Heat Islandmentioning
confidence: 99%
“…Net radiation = Incoming solar − Reflected solar + Atmospheric radiation − Surface radiation (3) Incoming solar represents the short-wave radiation emitted from the sun, which varies according to latitude, season, time of the day, clouds, etc. [25].…”
Section: Net Radiationmentioning
confidence: 99%
“…The urban heat island (UHI), as an indicator of urban climate modification, has been investigated extensively since it was first time documented by Luke Howard in 1818. The UHI phenomenon has been identified and recorded for most of the major cities in the world [1][2][3][4][5][6]. Evidence of the negative influences of UHI on energy consumption, air pollution, and public health began to accumulate decades ago.…”
Section: Introductionmentioning
confidence: 99%